Film studies : a global introduction (Routledge, 2019)
Film Studies: A Global Introduction reroutes film studies from its Euro-American focus and canon in order to introduce students to a medium that has always been global but has become differently and insistently so in the digital age. Glyn Davis, Kay Dickinson, Lisa Patti and Amy Villarejo's approach encourages readers to think about film holistically by looking beyond the textual analysis of key films. In contrast, it engages with other vital areas, such as financing, labour, marketing, distribution, exhibition, preservation, and politics, reflecting contemporary aspects of cinema production